Hubungan Status gizi dengan kejadian Diabetes Melitus pada Lansia di PSTW Budhi Dharma Bekasi Tahun 2013 - Asriah, Nurul (STIKes Medistra Indonesia, 2014)
ABSTRACTThe Corelation Nutritional Status with incidence of Diabetes Mellitus in elderly at PSTW Budhi Dharma Bekasi in 2013 Nurul Asriah Background : Increasing number of elderly involve life expectancy of elderly increase too. The impact of increase number of elderly, it can be seen from the pattern of degenerative disease like hypertention, ccoronaty heart disease and including Diabetes Mellitus alsa. More over, nutritional status can be influence the pattern of degenerative disease.Conlusion :Purpose in this research: to know the corelation Nutritional Status with incidence of Diabetes Mellitus in elderly at PSTW Budhi Dharma Bekasi in 2013Methode: Used analytic corelation with cross sectional, recruting sample by simple random sampling, ther were 86 respondets. Statistic test used Chi SquareResult: That there was a significant between nutritional Status with The Corelation Nutritional Status with incidence of Diabetes Mellitus in elderly at PSTW Budhi Dharma Bekasi in 2013 (P value 0.002 <α)The Result of research can be keeping and increasing healthy in elderly with caring nutritional status and life style in elderly. Keyword : Nutritional Status, Diabetes Mellitus, ElderlyReferences : 2002-2013Number Of Page : xii -56